THE EFFECT OF WORK-FAMILY CONFLICT AND JOB STRESS ON TURNOVER INTENTION - Saraswati, Vita Putri; Subudi, Made (E-Jurnal Manajemen, 2017)
This study aims to determine the effect of work-family conflict and job stress on employee TI at Harris Hotel Kuta Galleria, Bali. In this study, a population of 55 employees, because the population is relatively small, the census approach performed as a method of research, which uses the entire population as a respondent. Multiple linear regression analysis is used as a tool of analysis of this study. The results obtained in this study is that there is a positive and significant influence between work-family conflict on TI, as well as the existence of positive and significant influence between job stress on TI. The research has implications that the Harris Hotel Kuta Galleria reduce work-family conflict and job stress for employees that will impact on TI.
Keywords: work-family conflict, job stress, turnover intention